Kajian Adsorpsi Krom Dalam Limbah Cair Penyamakan Kulit - Hesty Eka Mayasari; Muhammad Sholeh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
Chromium in tannery wastewater is still a problem for the industry. Treatment of tannery wastewater using conventional way is not enough. Alternative wastewater treatment such as adsorption methods is needed. This review summarizes and discusses the state of the art of research on adsorbents in addition to commercial activated carbon for tannery wastewater treatment.